A residual modified transformation formula from munsell to sRGB color system. Issue 3 (18th March 2014) - Hsiao, Shih‐Wen; Tsai, Cheng‐Ju
Abstract A residual modified transformation formula from Munsell to sRGB color system is presented in this article. The development of the transformation formula is based on the 1625 Munsell color chips in the Munsell Renotation Data that could be displayed on the sRGB monitor. The developed transformation formula consists of two models, one is named as the corresponding matrix model and the other is the residual modified model. The corresponding matrix model was obtained using numerical analysis methods to map each chip color attribute values from Munsell to sRGB and then its corresponding matrix for each Hue was constructed. The residual modified model was obtained using the discrete cosine transform to construct a residual modified function, which was used to modify the transformation error of each chip after applying the corresponding matrix model. The transformed accuracy rate for the corresponding matrix model is 88.4% and for the residual modified model can be enhanced to 96.6% for all of the chips. The developed transformation formula can be applied to research in which Munsell colors are presented on the sRGB monitor. With the aid of these formulas, designers can show the advanced real‐time results on a sRGB monitor for the product's color planning based on Munsell color system. Therefore, this research has a great contribution on the practical application for color planning in product design. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 243–255, 2015